Penanaman Nilai-Nilai Pendidikan Agama Islam Pada Taman Pendidikan Al-Qur’an Al-Hikmah - Ariya, Japa Ariya Kurunika; Surawan; Asmail Azmy (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research stems from the difference in the delivery of learning material between the TPQ Al-Hikmah and the other TPQ-TPQ, which are generally only material about how to read the Al-Qur'an and write it properly and correctly. However, in the TPQ Al-Hikmah, apart from reading the Al-Qur'an material and how to write it, it is also conveyed about the inculcation of PAI values in the materials of Aqidah, Morals, Fiqh, Al-Qur'an/Tajwid, and SKI So it is hoped that later the students will have extensive Islamic religious knowledge. By using a descriptive qualitative research method, this research will dig deeply about the inculcation of what PAI values are in the Al-Hikmah TPQ. As for knowing the purpose of inculcating what PAI values are in TPQ Al-Hikmah a. Allah has power over everything in aqidah material, b. must have praiseworthy morals in daily interactions on moral material, c. perform worship properly in accordance with the religious law on fiqh material, d. must be able to read the Al-Qur'an properly and correctly, and e. imitating the characteristics of the Prophet Muhamad SAW in everyday life.